(untitled) (Research, Society and Development, 2023)
In Brazil, the Ministry of Health considers rare diseases that affect up to 65 people in every 100,000 individuals. Among these diseases are the genodermatoses, which constitute a heterogeneous group of diseases that primarily or exclusively affect the skin. Difficult to diagnose, the treatment is often ineffective. This mini bibliographic review aims to discuss the true potential of tissue engineering in the treatment of rare diseases. It is worth noting that regenerative medicine and tissue engineering have facilitated the development of therapeutic alternatives for replacing and/or repairing affected areas in these patients, including the use of biomaterials and specific cell types. Biomaterials must be biocompatible, bioresorbable, mechanical compatible with the target site, and provide adequate support to enable the growth of new tissue in vivo and in vitro, as well as facilitate the transport of biomolecules to induce cellular responses. Cells, on the other hand, must have differentiation potential and function as if they were in their natural environment. Tissue engineering can contribute to the treatment of rare diseases in two ways: 1) by developing devices that can mimic the function of affected tissues and aid in drug screening, and 2) by creating structures that can be directly used in therapeutic processes. Therefore, there is a genuine potential for the application of tissue engineering in the treatment of rare diseases. This review can be valuable, even as a starting point for researchers working in this field.